EKSISTENSI REKAMAN VIDEO DALAM KASUS TINDAK PIDANA PERZINAAN MENURUT HUKUM ISLAM - Isnu Cut Ali; Muhammad Yunus (Al-Madaris Jurnal Pendidikan dan Studi Keislaman, 2022)
Evidence has a significant position in the court process, where this evidence becomes a means that can be used to strengthen arguments in a trial in court. Therefore, this evidence should not be left behind if someone wants to prove a case in a court case, both involving criminal cases and civil cases. Evidence takes various forms, according to cultural developments and times. In the past, there was never any audio-visual electronic evidence, but now it is visible in our lives, such as video camera recordings. Some of the recordings are positive that educate, and some are negative that are not educational, such as recordings of lewd scenes (porn films) which are often exposed by the masses through the internet or multimedia player devices that function to play CD/VCD/DVD recordings of these lewd scenes. Ironically, it turns out that the actors in the scene are Muslims who are carried away by the flow of promiscuity in the midst of the life of the nation and state which tends to be secularistic-individualistic. In this study the author examines three things. First, the cause and wisdom of adultery is forbidden in Islam; Second, the provisions of the procedural law for proving the crime of adultery in Islam; and Third, the position of the evidence of video camera recordings related to the crime of adultery according to the procedural law of proof in Islam. Thus, the author hopes that this study will provide comprehensive benefits regarding the criminal case of adultery and the procedural law applicable in Indonesia for the perpetrators.